Component performance and systems applications of surface acoustic wave devices - International Specialist Seminar on Component Performance and Systems Applications of Surface Acoustic Wave Devices (1973 : Aviemore, Scotland); Institution of Elctrical Engineers. Electronics Division (London : IEE, 1973)
13